2017
DOI: 10.1186/s13063-017-2274-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of robot-assisted training added to conventional rehabilitation in patients with humeral fracture early after surgical treatment: protocol of a randomised, controlled, multicentre trial

Abstract: BackgroundThe incidence of proximal humeral fractures increases with age. The functional recovery of the upper arm after such fractures is slow, and results are often disappointing. Treatment is associated with long immobilisation periods. Evidence-based exercise guidelines are missing. Loss of muscle mass as well as reduced range of motion and motor performance are common consequences. These losses could be partly counteracted by training interventions using robot-assisted arm support of the affected arm deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Due to the funding guidelines of the sponsor of the study (“Deutsche Gesetzliche Unfallversicherung (DGUV)”) only persons up to 69 could be included into the intervention study. This decision is based on the study approach to be able to quickly re-integrate patients after PHF into everyday work [19]. The second group consisted of 40 patients with an age range from 34 to 69 years with surgical treatment after PHF participating in a randomised controlled trail to measure the effectiveness of robot-assisted training added to conventional rehabilitation [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the funding guidelines of the sponsor of the study (“Deutsche Gesetzliche Unfallversicherung (DGUV)”) only persons up to 69 could be included into the intervention study. This decision is based on the study approach to be able to quickly re-integrate patients after PHF into everyday work [19]. The second group consisted of 40 patients with an age range from 34 to 69 years with surgical treatment after PHF participating in a randomised controlled trail to measure the effectiveness of robot-assisted training added to conventional rehabilitation [19].…”
Section: Methodsmentioning
confidence: 99%
“…This decision is based on the study approach to be able to quickly re-integrate patients after PHF into everyday work [19]. The second group consisted of 40 patients with an age range from 34 to 69 years with surgical treatment after PHF participating in a randomised controlled trail to measure the effectiveness of robot-assisted training added to conventional rehabilitation [19]. The proximal humeral fractures of both patient groups were surgically fixed by plate osteosynthesis, screw fixation, endoprostheses or humeral nails.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, even if some of the rehabilitation robots reported for neurorehabilitation could have the potential use in orthopaedic rehabilitation, the adopted human-robot interaction schemes and assisted physiotherapy approaches of such systems cannot be directly applied for the needs of orthopaedic patients [ 40 , 41 ]. At most, they should be used with precaution, but in any case, it is not clear if neurorehabilitation approaches would be valid for orthopaedic lesions, given the noticeable different clinical goals [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were able to engage with the VR system and complete the interventions without premature withdrawal or non-adherence. A previous study has emphasized the importance of robot-assisted rehabilitation in the acute phase after musculoskeletal injuries and reported that it allowed the patient to mobilize the affected arm early by reducing muscle mass loss and improving motor capacity [22]. Immobilization after burn injuries induces loss of muscle strength and flexibility in adjacent joints.…”
Section: Discussionmentioning
confidence: 99%